Moving toward implementation: basin-wide modeling and stakeholder platforms in the Incomati Basin - Joaquim, D.; van der Merwe, S.; Nehring, Ryan; Lautze, Jonathan F. (International Water Management Institute, 2024)
NEXUS Gains has been in partnership with INMACOM for more than two years, providing technical support for integrated management of the Incomati’s natural resources. One key focus of this collaboration is a basin-wide decision-support system, with another being the development of a multi-stakeholder platform. Both were the subject of a workshop in South Africa in November 2024, where discussions with stakeholders highlighted the significant impact of NEXUS Gains’ work.